Improving High School Students’ Awareness through Safety riding Training: A Case Study at SMA Negeri 1 Pagelaran - Susanto, Try; Budiman, Arief (MEKONGGA: Jurnal Pengabdian Masyarakat, 2025)
Road safety is an important issue that greatly affects teenagers, including high school students. The lack of formal education on safe riding practices in schools became the basis for this community service activity. This program aims to improve students’ knowledge and awareness of safe riding through training that includes theoretical sessions, simulations, and hands-on practice. The activity was carried out at SMA Negeri 1 Pagelaran, involving students, teachers, traffic police officers (Satlantas), and local motorcycle communities. The training methods consisted of interactive seminars, case discussions, riding technique demonstrations, and evaluation through pre- and post-tests. The evaluation showed an average increase of 45% in students’ understanding after the training. This activity helped shape more responsible riding behavior and provided impactful experiential learning. Similar programs are recommended to be implemented regularly in schools as a preventive effort to reduce traffic accidents among students